Alea Iacta Est: The Kampala Amendment on the Crime of Aggression Post-2017: A Response to Koh and Buchwald. (2015) - Zimmermann, Andreas
Abstract : Having embarked in 49 BCE on his long war against Pompey, Julius Caesar reportedly commented "alea iacta est"—events have passed a point of no return. With the adoption and uptake of the Kampala amendment on the crime of aggression the Rubicon has also been crossed with twenty-six states (i.e. merely four less than the required quorum) having ratified the amendment. A significant further number of states have ratified the Rome Statute after the adoption of the Kampala amendment, posing the interesting question whether they ought to be counted towards that quorum.